Physical profile of Partizani team in Greco-Roman wrestling for youngsters - Zylfi, S.; Avni, H.; Ermir, H.; Perparim, F. (Science, Movement & Health, 2013)
Purpose. The goal of this research is to understand and analyze the physical skills of the Greco-Roman wrestling team, applying a systematic scientific procedure. Through various physical tests that we will apply, we aim at arriving to results that will reflect the current state of the wrestlers and the new opportunities for all weight categories. These results will help us to compare the youngsters` results with those of the professionals and FILA's standards. Methods. The youngsters are of age 18-21 years, were various physical tests will be used and all possible results for each category will be recorded. For the realization of this study we consult the various literature and studies by international and national authors. The data obtained from the tests were processed in Excel and the various tables and graphics were constructed. Results. After processing the data of the tests for the following components: aerobic power, speed and power, speed endurance, speed strength, strength endurance, dynamic strength endurance, flexibility and special mobility; we notice that the wrestlers of light and medium weight are faster than those of heavy weights especially in such tests where body weight is the primary determinant e.g. rope climbing or gymnastic iron. Also, the wrestlers of light weights quickly perform actions typical of the sport of wrestling, such as Dummy Throws. This is explained by their relative strength compared to those of heavy weights. Interesting are the results of the sprint, which is predominates by those weighting 84 kg. Perhaps this is related to the great muscular mass those wrestlers of this weight have, yet it remains to be confirmed in future studies. Conclusions. The results of this study can serve as a guide for all wrestling coaches, who can use these results for a more harmonious preparation of their athletes. Having said that, the study has applicable implication and serves to increase the quality of sports in this discipline.